Non-Western perspectives on human communication implications for theory and practice - Kim, Min-Sun.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2002)
Min-Sun Kim challenges the longstanding individualistic model on which most Western intercultural research is based. She proposes a new way of conceptualizing identity by blending traditional and non-Western views into a broader, more realistic understanding of cultures and communication.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intercultural communication; Communication and culture; Electronic books